Portal of the Pacific and Tower of the Sun, California World's Fair on San Francisco Bay (Stanley A. Plitz Company)
Two massive Elephant Towers flank the Portals of the Pacifica - the main entrance to the Fair. The Towers are 120 feet high and are surmounted by three elephant motives, - age-old symbols of pageantry. In the background, is the magnificent gleaming 400 foot Tower of the Sun.